2023
DOI: 10.1002/jmv.28730
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic immunogenicity after primary and booster inactivated SARS‐CoV‐2 vaccination in people living with HIV: A longitudinal observational study

Abstract: People living with HIV (PLWH) have poor outcomes from severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2); vaccination reduces the associated mortality. The humoral immune response dynamics after booster inactivated vaccinations in PLWH remain unclear. In this longitudinal observational study, 100 PLWH after primary inactivated SARS-CoV-2 vaccination were consecutively recruited and followed up. After booster vaccination (BV), neutralizing antibodies (NAbs) were detected at 1 month from all the PLWH, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…PWH mounted equally robust immunity following vaccination and even more robust stronger immunity was observed in both groups following naturally acquired SARS-CoV-2 infection [18] Based on quantile regression with an interaction term between HIV status and COVID infection status and adjusted for age, sex, race (white/black/ other), multimorbidity (!2 comorbidities), vaccine type and time between vaccine doses. and the titre increased six-fold compared with that associated with the primary vaccination, similar to what was observed in HIV-negative controls [19]. Neutralizing antibody titre declined over time after booster vaccine but remained higher at 6 months than following primary vaccine [19].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…PWH mounted equally robust immunity following vaccination and even more robust stronger immunity was observed in both groups following naturally acquired SARS-CoV-2 infection [18] Based on quantile regression with an interaction term between HIV status and COVID infection status and adjusted for age, sex, race (white/black/ other), multimorbidity (!2 comorbidities), vaccine type and time between vaccine doses. and the titre increased six-fold compared with that associated with the primary vaccination, similar to what was observed in HIV-negative controls [19]. Neutralizing antibody titre declined over time after booster vaccine but remained higher at 6 months than following primary vaccine [19].…”
Section: Discussionsupporting
confidence: 74%
“…Third dose vaccines elicited better neutralizing antibody responses in PWH with longer time intervals between vaccines [30]. Furthermore, although there is evidence for sex-based differences in humoral immune response with certain types of vaccinations in HIV-negative populations [30], we and others have not observed any sex difference in antibody level or neutralization capacity in the context of COVID-19 vaccination [10][11][12]19]. Moreover, in both PWH vs. HIV-negative controls, some participants had a high antibody titre but low ID50.…”
Section: Discussionmentioning
confidence: 60%
“…A total of seven eligible studies ( 43 , 47 , 51 , 53 , 54 , 59 , 61 ) involved PLWH with T-cell counts < 200, none of which had HC. The results showed a pooled IRR of 86.27% (95% CI, 65.35–99.07).…”
Section: Resultsmentioning
confidence: 99%
“…For now, there are several boost studies have demonstrated favorable immunogenicity and efficacy of COVID‐19 vaccines in PLWH 17–22 . The boosting vaccination in PLWH was safe and greatly increased the immune response with respect to the primary vaccination 16 .…”
Section: Introductionmentioning
confidence: 99%
“…For now, there are several boost studies have demonstrated favorable immunogenicity and efficacy of COVID-19 vaccines in PLWH. [17][18][19][20][21][22] The boosting vaccination in PLWH was safe and greatly increased the immune response with respect to the primary vaccination. 16 The antibody levels in PLWH postvaccination maintained for at least 3 months, but PLWH with lower CD4+T-cell counts showed a poor antibody response to the inactivated vaccines.…”
Section: Introductionmentioning
confidence: 99%